PELATIHAN COMPUTATIONAL THINKING SECARA UNPLUGGED KEPADA GURU PAUD PPT MUTIARA BUNDA ONDOMOHEN - Anggraini, Kristin; Kriesye S, Maria Josephine; Haryanto, Jessica Febrina; Anugerah Wati, Sindy (Jurnal Abdimas Bina Bangsa, 2025)
The aim of this community service activity (Abdimas) is to provide training to PPT Mutiara Bunda Ondomohen teachers to get to know the basic concepts of Computational Thinking (CT) and to infuse them in the subjects taught so that they can provide CT skills to solve complex problems in everyday life -student day. The partners in community service activities are the mothers of PPT Mutiara Bunda Ondomohen PAUD, totaling 4 people. The implementation of this community service activity was carried out over 8 meetings within one month and consisted of 2 stages, namely the stage of introducing CT and making educational game tools (APE) that support CT in learning as well as the stage of using CT-based APE media in the classroom. The conclusion is that the training carried out for PPT Mutiara Bunda Ondomohen teachers can improve the teachers' skills in infusing CT into subjects.